Wearable GPS Devices in a British Elite Soccer Academy Setting: A Foucauldian Disciplinary Analysis Of Player Development And Experience - Luke Jones (Bowling Green State University, 2019)
Conventional wisdom dictates that the use of GPS surveillance technology in sport to assist athletic performance is an overwhelminglypositive phenomenon. Specifically, the health and performance benefits of the application of GPS and surveillance technologies have been well documented across a range of field sports. Previous research into the developmental implications of GPS surveillance in professional rugby league (Jones, Marshall, & Denison, 2016) has identified that there are some significant unintended consequencesof their use for elite athletes. We utilised the disciplinary analysis of Foucault to investigate the experiences of academy soccer playersin relation to wearable GPS technology. Five academy players took part in semi-structured group interviews as part of a wider study into the effects of surveillance technologies within an academy setting. We suggest that the now normalised and increasingly ubiqui- tous use of GPS surveillance technology within this particular British soccer academy is seen as relatively insignificant by its players. However, we also report that GPS use does act to impose discipline on academy players and may well have unforeseen and potentially problematic implications for academy players' development experience.